The Financial Sector and Sustainable Development - A Review of Selected Environmental Practices Implemented in Financial Institutions Operating in Poland Between 2016 and 2020 - Kozar, Łukasz Jarosław (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The main objective of the article is to present the directions of pro-environmental activities undertaken by institutions from the financial sector operating in Poland and their significance for green transformation of the economy. In turn, an additional aim of the analysis undertaken is to show whether financial institutions have instruments that are typical for them, but at the same time are aimed directly at the process of greening the economy. Methodology: The study is of a theoretical and analytical character. In addition to a review of available domestic and foreign literature on the subject, selected good environmental practices implemented in financial sector institutions in Poland in 2016–2020 were analysed. Qualitative data analysis (content analysis of good practices) was applied. Results of the research: 94 good environmental practices from 24 financial sector institutions were analysed. Different subject and object orientations of the good practices were observed. It was found that through the implementation of environmental activities, financial institutions can build a positive image in their surroundings. In terms of issues related to green transformation, a special role was assigned to banks, which can offer green banking products. Products of this type are directly aimed at supporting investments whose role is to change the existing way of economy to a more sustainable one.